Multiplex PCR to discriminate bovine, porcine, and fish DNA in gelatin and confectionery products - Sultana, Sharmin; Hossain, Motalib A.Motalib; Sarker, Md. Zaidul Islam; Ali, Md Eaqub (Academic Press Inc., 2018)
Gelatin is widely used in many confectionery products such as gummy, candies, pastilles and marshmallows. However, the acceptance of gelatin in consumer goods largely depends on its animal origins. The main sources of gelatin are pig, cow and fish collagens that have differential acceptance in Halal, Kosher and Hindu foods. Currently, several simplex and duplex PCR assays are available for the determination of gelatin origins but those methods are not only time-consuming and costly but also cannot reveal all information in a single assay platform. For the first time, we documented here a tetraplex PCR assay involving eukaryotic, fish, bovine, and porcine control for the simultaneous detection of these species by a single, easy and reliable approach. The assay was optimized under pure and mixed gelatin matrices and validated by PCR product sequencing. Finally, 38 halal branded confectionery items were screened and 33, 2 and 3 of them yielded positive bands for bovine, porcine and eukaryotes, respectively. The detection limit was 0.1 to 0.001 ng DNA extracted from pure and mixed gelatins. The study is potentially useful in monitoring and certifying halal, kosher and vegetarian issues in processed foods, pharmaceuticals and cosmetics.